Impact of crown and inlay size variations on the accuracy of various digital impression techniques - Xia Wu; Haigang Shao; Yimei Qi; Xusheng Wu; Jiawen Kong; Meng Chu; Yuchuan Xu; Qixuan Huang; Heng Bo Jiang; Jae Mok Lee; Qi Chen (Scientific Reports)
Abstract Accurate digital impressions are crucial in modern dentistry, particularly for capturing fine details of various dental preparations. This study aimed to evaluate the effect of variations in the sizes of crown and inlay specimen on the accuracy of three digital impression techniques. Nine crown and nine inlay specimens were fabricated according to American Dental Association Standard No. 132. Gold standard measurements were obtained using a coordinate-measuring machine. Digitized files were generated using three impression techniques (n = 10): intraoral scanner (IOS), extraoral scanner with alginate (EOS-A), and extraoral scanner with silicone rubber (EOS-S). Digital models from EOSs served as reference sets for three-dimensional (3D) fitting analysis. Statistical analysis was conducted using one-way analysis of variance and Tukey’s post-hoc test. Specimen size variations significantly affected the accuracy of all impression techniques (p < 0.05). IOS exhibited superior accuracy across all specimens, with most trueness values falling within the clinical threshold. EOS-S demonstrated moderate trueness, meeting the threshold for most indexes, except the ra index in A2 and C1 crowns. EOS-A met the threshold only for A3 crown. All techniques achieved clinical precision thresholds, except for the rd index of A1 in the EOS-A inlay specimens, for which a slight exceedance was observed. Additionally, 3D fitting analysis revealed more pronounced deviations in the EOS-A group. The accuracy of digital impressions technique is influenced by variations in the size of crowns and inlays. This study highlights the significant impact of specimen size on the accuracy of digital impression techniques, providing valuable insights for enhancing restorative dentistry outcomes.